Comparison of recognition about denture adhesive between Japanese and Indonesian dentists: A pilot study - Shinsuke Sadamori; Taizo Hamada; Guang Hong; Nakai Nakai; Makoto Kawamura; Arifzan Razak (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
The purpose of this study was to compare cross-national differences of the recognition of denture adhesive among dentists. The design of the research was cross-cultural differences. The research was done in Japan and Indonesia. One hundred and ten dentists from Japan and Indonesia were surveyed using a questionnaire regarding knowledge/comprehension of denture adhesive (in Japanese and Indonesian versions respectively). Logistic regression model (forward stepwise method) showed that it was possible to distinguish Japanese dentists from Indonesian peers with a probability of 96.0 per cent by using 4 items out of 16. For the question of